Description of Two Species of Early Branching Dinoflagellates, Psammosa pacifica n. g., n. sp. and P. atlantica n. sp - Okamoto, Noriko (Public Library of Science, 2012)
In alveolate evolution, dinoflagellates have developed many unique features, including the cell that has epicone and hypocone, the undulating transverse flagellum. However, it remains unclear how these features evolved. The early branching dinoflagellates so far investigated such as Hematodinium, Amoebophrya and Oxyrrhis marina differ in many ways from of core dinoflagellates, or dinokaryotes. Except those handful of well studied taxa, the vast majority of early branching dinoflagellates are known only by environmental sequences, and remain enigmatic. In this study we describe two new species of the early branching dinoflagellates, Psammosa pacifica n. g., n. sp. and P. atlantica n. sp. from marine intertidal sandy beach. Molecular phylogeny of the small subunit (SSU) ribosomal RNA and Hsp90 gene places Psammosa spp. as an early branch among the dinoflagellates. Morphologically (1) they lack the typical dinoflagellate epicone–hypocone structure, and (2) undulation in either flagella. Instead they display a mosaïc of dinokaryotes traits, i.e. (3) presence of bi-partite trychocysts; Oxyrrhis marina–like traits, i.e. (4) presence of flagellar hairs, (5) presence of two-dimensional cobweb scales ornamenting both flagella (6) transversal cell division; a trait shared with some syndineansand Parvilucifera spp. i.e. (7) a nucleus with a conspicuous nucleolus and condensed chromatin distributed beneath the nuclear envelope; as well as Perkinsus marinus -like features i.e. (8) separate ventral grooves where flagella emerge and (9) lacking dinoflagellate-type undulating flagellum. Notably Psammosa retains an apical complex structure, which is shared between perkinsids, colpodellids, chromerids and apicomplexans, but is not found in dinokaryotic dinoflagellates.